2015
DOI: 10.14800/rd.472
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-133α regulates neurotensin-associated colonic inflammation in colonic epithelial cells and experimental colitis

Abstract: Ulcerative colitis (UC) and Crohn’s Disease (CD) are the two most common forms of Inflammatory Bowel Diseases (IBD) marked by chronic and persistent inflammation. Neurotensin (NT), together with its receptor, NT receptor 1 (NTR1), are important mediators in intestinal inflammation and their expression is upregulated in the intestine of experimental colitis models and UC colonic biopsies. MicroRNAs (miRNAs) are short, non-coding RNA molecules which act as transcription repressors. We have previously shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…21,2932 In epithelial cells, miR-133a is upregulated by neurotensin to mediate colonic inflammation. 33 In this study, we further demonstrated that GCH1 mRNA is a target of miR-133a in endothelial cells. Although GCH1 gene expression is regulated posttranslationally, such as by the ubiquitin-proteasome pathway and phosphorylation, 25,34,35 this study is the first to ascertain that GCH1 mRNA stability is determined by miR-133a.…”
Section: Discussionsupporting
confidence: 63%
“…21,2932 In epithelial cells, miR-133a is upregulated by neurotensin to mediate colonic inflammation. 33 In this study, we further demonstrated that GCH1 mRNA is a target of miR-133a in endothelial cells. Although GCH1 gene expression is regulated posttranslationally, such as by the ubiquitin-proteasome pathway and phosphorylation, 25,34,35 this study is the first to ascertain that GCH1 mRNA stability is determined by miR-133a.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have found that miR-133a is a muscle-specific miRNA that plays an essential role in the normal development and function of the skeletal muscle and myocardium ( 38 , 39 ). In addition, epithelial cell miR-133a expression has been reported to be upregulated by neurotensin, which mediates colitis ( 40 ). The present study found that miR-133a can regulate the transcript levels of the anti-apoptotic protein Bcl-xL, thereby highlighting its role in the process of endothelial cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A 13 amino acid length neuropeptide, neurotensin (NT), together with its high affinity G protein-coupled receptor 1 (NTR1), are believed to promote the development of UC and are expressed in the colon where they are upregulated in animal colitis models and UC patients 51 54 . NT/NTR1 signaling is involved in various colonic responses, including proinflammatory responses, and regulates several miRNAs associated with intestinal inflammation 55 , 56 . Law et al 57 investigated the effect of NT stimulation on the lncRNA profile of human colonic epithelial cells (NCM460) with NTR1 overexpression.…”
Section: Ccat1 and Uca1mentioning
confidence: 99%